1998
DOI: 10.1021/np970586b
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Isoflavans from Eysenhardtia polystachya

Abstract: Two new cytotoxic isoflavans, (3S)-7-hydroxy-2',3',4',5', 8-pentamethoxyisoflavan (1) and (3S)-3',7-dihydroxy-2',4',5', 8-tetramethoxyisoflavan (2), were isolated from the bark and trunks of Eysenhardtia polystachya (Leguminosae), together with the known constituents stigmasterol, isoduartin, cuneatin, 7-hydroxy-2',4', 5'-trimethoxyisoflavone, and 3,4-dimethoxy-8, 9-(methylenedioxy)pterocarpan. The structures of 1 and 2 were elucidated on the basis of spectroscopic methods. The antimicrobial, cytotoxic, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…This was further supported by the UV spectrum, which exhibited bands at 218 and 284 nm [13]. The 1 H NMR spectrum of 1 also revealed four aromatic protons at G 6.61 (d, J = 8.5 Hz), 6.38 (d, J = 8.5 Hz), 6.79 (d, J = 8.5 Hz), and 6.57 (d, J = 8.5 Hz), in addition to singlets of three methoxyl groups at G 3.47, 3.86, and 3.87.…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…This was further supported by the UV spectrum, which exhibited bands at 218 and 284 nm [13]. The 1 H NMR spectrum of 1 also revealed four aromatic protons at G 6.61 (d, J = 8.5 Hz), 6.38 (d, J = 8.5 Hz), 6.79 (d, J = 8.5 Hz), and 6.57 (d, J = 8.5 Hz), in addition to singlets of three methoxyl groups at G 3.47, 3.86, and 3.87.…”
mentioning
confidence: 65%
“…Identification of the NOE interaction between H-6 and the methoxyl group at G 3.47 linked to C-7 (at G 152.2 by HMBC), between H-4c and the methoxyl group at G 3.86 linked to C-5c (at G 146.5, by HMBC), between the methoxyl at G 3.87 linked to C-6c (at G 145.2, by HMBC) and the methoxyl group at C-5c, and between H-3c and the aldehydic moiety at G 10.30 linked to C-2c (at G 138.8, by HMBC) further allowed us to confirm the positions of various substituents. The CD curve of 1 indicating the 3S configuration showed a negative Cotton effect in the 262-290 nm region [13]. Thus, on the basis of these evidences, colutin (1) was assigned the structure (3S)-8-(6cc-methyl-5cc-heptenyl)-2c-aldehyde-5c,6c,7-trimethoxyisoflavan.…”
mentioning
confidence: 88%
“…This tree gained attention due to its blue fluorescence as a result of its infusion in water, and by its biological properties, including antidiabetic, antibacterial, antioxidant, among others [36,37]. Many studies have reported the principal components of EP extracted using methanol, ethanol and water as solvents [35,36,38,39]. In this way, the responsible compounds for the fluorescence of EP are Coatline A and Coatline B,…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…12) Previous studies on Eysenhardtia species have highlighted the hypoglycemic activity of E. polystachya 13) and the antihyperglycemic activity of E. platycarpa, 14) as well as the isolation of cytotoxic flavonoids 15,16) and 3-O-acetyloleanolic acid [which displayed antihyperglycemic activity in streptozotocin (STZ)-induced diabetic rats 14) ]. As part of our screening of plants for the isolation of substances with antioxidant and antihyperglycemic potential, 14,17) this study was conducted to A) assess the antioxidant effects of extracts from E. platycarpa, E. punctata, and E. subcoriacea, as well as of compounds 1-8, natural constituents isolated from E. platycarpa (Chart 1), in a rat pancreas model and in a 1,1 diphenyl-2-picrylhydrazyl (DPPH) radical scavenger assay; B) synthesize 1, which displayed a protective effect against 2,2-azo-bis(2-amidinopropane)dihydrochloride (AAPH)-induced damage in pancreatic homogenate; and C) evaluate the protective effect of 1 in STZinduced diabetic rats.…”
Section: )mentioning
confidence: 99%